Analysis of amino acid and codon usage inParamecium bursaria. Issue 20 (1st September 2015) - Dohra, Hideo; Fujishima, Masahiro; Suzuki, Haruo
Abstract : The ciliate Paramecium bursaria harbors the green‐alga Chlorella symbionts. We reassembled the P. bursaria transcriptome to minimize falsely fused transcripts, and investigated amino acid and codon usage using the transcriptome data. Surface proteins preferentially use smaller amino acid residues like cysteine. Unusual synonymous codon and amino acid usage in highly expressed genes can reflect a balance between translational selection and other factors. A correlation of gene expression level with synonymous codon or amino acid usage is emphasized in genes down‐regulated in symbiont‐bearing cells compared to symbiont‐free cells. Our results imply that the selection is associated with P. bursaria – Chlorella symbiosis. Abstract : We reassembled Paramecium bursaria transcriptome to minimize falsely fused RNAs. In P. bursaria, surface proteins preferentially use smaller amino acid residues. In P. bursaria, highly expressed genes have unusual amino acid and codon usage. Translational selection may be associated with P. bursaria – Chlorella symbiosis.